2012
DOI: 10.2460/ajvr.73.8.1299
|View full text |Cite
|
Sign up to set email alerts
|

Refractive state following retinal reattachment and silicone oil tamponade in dogs

Abstract: Hyperopia was observed in all dogs that underwent SiO tamponade, regardless of lens status (phakic, pseudophakic, or aphakic). Aphakic eyes underwent a myopic shift when filled with SiO. Pseudophakic eyes appeared to be more hyperopic than phakic eyes when filled with SiO; however, additional investigation is needed to confirm the study findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A large study in humans showed that 2 months after RRS, the visual acuity was ≥20/40, 20/50–20/100, and ≤20/200 in 51%, 17%, and 32% of patients, respectively . In this context, one should remember that the visual acuity of healthy, emmetropic dogs is about 20 of 75, and that this acuity is reduced postoperatively due to the 2.7–3.2 diopter hyperopia induced in canine patients by the silicone oil . Therefore, it is very likely that the postoperative vision in many of our patients was far from fully recovered, but functional vision with improved quality of life was achieved in most dogs.…”
Section: Discussionmentioning
confidence: 96%
“…A large study in humans showed that 2 months after RRS, the visual acuity was ≥20/40, 20/50–20/100, and ≤20/200 in 51%, 17%, and 32% of patients, respectively . In this context, one should remember that the visual acuity of healthy, emmetropic dogs is about 20 of 75, and that this acuity is reduced postoperatively due to the 2.7–3.2 diopter hyperopia induced in canine patients by the silicone oil . Therefore, it is very likely that the postoperative vision in many of our patients was far from fully recovered, but functional vision with improved quality of life was achieved in most dogs.…”
Section: Discussionmentioning
confidence: 96%
“…We used normal beagle dogs for this study because dogs have been frequently used in other studies for preclinical testing of medical devices such as artificial joints. In addition, there have been reports on cataract surgery in dogs [ 17 ] as well as vitrectomy to treat retinal detachment in dogs [ 4 , 6 , 18 , 19 ] at veterinary clinical settings. An experimental study which used dogs for vitrectomy was also described [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is compatible with literature data about refractive changes with silicone oil fill, which are either hyperopic or myopic, depending on the lens status. 13 15 …”
Section: Discussionmentioning
confidence: 99%